Patient-reported gastrointestinal symptoms following surgery for gastric cancer and the relative risk factors - Xu, Rui; Gu, Qiong; Xiao, Shuomeng; Zhao, Ping; Ding, Zhi (Frontiers in Oncology, 2022)
Purpose：The study aims to assess the incidence of short term patient-reported postoperative gastrointestinal symptoms (PGISs) after gastric cancer surgery, and explore the relative risk factors for the symptoms. Methods: Patients with radical gastrectomy were included for this retrospective and observative study. Symptoms extracted from the MD Anderson Symptom Inventory Gastrointestinal Cancer Module (MDASI-GI) were collected in post-discharge week (PDW) 1 and postoperative month (POM) 1. The distributing states of symptoms were analyzed in PDW1 and POM1. Logistic regression models were used to identify risk factors for PGISs. Results: Among 356 patients with complete interviewee, 156 (43.8%) patients reported abdominal distention in PDW1, and which were significantly higher than patients in POM1 (103(28.9%), p<0.001). pain (15.2% vs 9.8%), dysphagia (5.6% vs 7.0%), diarrhea (3.7% vs 3.4%), vomiting (2.5% vs 2.8%) had no significant differences between PDW1 and POM1. Logistic models found that risk factors for PGISs were total gastrectomy (odds ratio [OR]:1.948; 95%CI: 1.097-3.459; p=0.023); disturbed sleep (OR:3.116; 95%CI: 1.831-5.303; p<0.001) in PDW1; and female (OR:1.726; 95%CI: 1.071-2.782; p=0.025); total gastrectomy (OR:1.729; 95%CI: 1.055-2.834; p=0.030); disturbed sleep (OR:3.533; 95%CI: 1.757-7.106; p<0.001) in POM1. Conclusions: The main symptom after gastric cancer surgery was abdominal distention, total gastrectomy and disturbed sleep were the relative risk factors for gastrointestinal symptoms after gastric cancer surgery. Attention to postoperative symptoms and related factors may assist clinical decision-making and timely symptom intervention may improves the quality of life of post gastrectomy patients.